O léxico toponímico nos domínios de Dona Joaquina de Pompéu - Joara Maria de Campos Menezes (2009)
This research has as main objective to study the toponyms of the region concerning the cities of Pitangui, Pompéu and Papagaios, an old area under the control of Dona Joaquina de Pompéu, who was an important farmer from the Alto do São Francisco region and was also known as a great colaborator in the development of animal husbandry in Minas Gerais state in the 18th and 19th centuries. We contribute, with this proposition, to give a greater visibility to a sociocultural analysis of the region, once the linguistic study of the place names opens to thepossibility of recovering a part of the local history and culture from a comunity. As the theoretical and methodological reference, we adopted the toponymic models of Dauzat (1926), Dick (1990a) and Dick (1990b), and the environment and culture concepts of Diégues Junior (1960), Sapir (1969) and Lyons (1981). Beneath the labovian sociolinguistic model, we started from the present to the past and came back through oral interviews, old documents and geographic letters from old and contemporaneous times. Using these documents, we wereable to observe cases of linguistic variability, change and retention. The analysis of the data reflected the historical and cultural environment of the agricultural region of the 17th-century Minas, which was mainly occupied by paulistas, right after the episode known as the Emboabas. The predominance of the physical nature elements, with a special highlight for the names of plants (or fitotoponyms), shows the name-calling attachment between the man and the nature.